Lakaki As a Form of Curriculum Adaptation for Learning Electrical Circuits Material for the Sixth Grade Students of SD Negeri Demakijo 2 Sleman Regency Academic Year 2023/2024 - Sutarti S; Ana Fitrotun Nisa; Berliana Henu Cahyani (Universitas Pendidikan Indonesia (UPI), 2023)
Science learning in elementary schools is influenced by, among other things, interactive learning experiences. Interactive learning involves the activities of all students with various characteristics. An interactive learning experience will support the successful learning outcomes of all students. In reality, teachers face a diversity of student characteristics, one of which is related to different cognitive abilities. The aim of this research is to determine the success of the learning outcomes of all students through the Lakaki